2023
DOI: 10.1038/s41598-023-31177-8
|View full text |Cite
|
Sign up to set email alerts
|

Clinical evaluation of DIAGNOVIR SARS-CoV-2 ultra-rapid antigen test performance compared to PCR-based testing

Abstract: Coronavirus Disease-19 (COVID-19) is a highly contagious infectious disease caused by the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). The development of rapid antigen tests has contributed to easing the burden on healthcare and lifting restrictions by detecting infected individuals to help prevent further transmission of the virus. We developed a state-of-art rapid antigen testing system, named DIAGNOVIR, based on immune-fluorescence analysis, which can process and give the results in a minut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 45 publications
(61 reference statements)
0
3
0
Order By: Relevance
“…These symptomatic individuals were likely to be confirmed as SARS-CoV-2 infection in real-life applications [ 27 ]. On the other hand, asymptomatic individuals at the screening point would likely be pre-symptomatic or infected without developing symptoms [ 28 ]. Therefore, it is thus necessary to confirm SARS-CoV-2 status by performing tests periodically with asymptomatic people in correctional facilities [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…These symptomatic individuals were likely to be confirmed as SARS-CoV-2 infection in real-life applications [ 27 ]. On the other hand, asymptomatic individuals at the screening point would likely be pre-symptomatic or infected without developing symptoms [ 28 ]. Therefore, it is thus necessary to confirm SARS-CoV-2 status by performing tests periodically with asymptomatic people in correctional facilities [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…A study on several currently available RAT kits demonstrated a similar level of sensitivity to Omicron and non-Omicron variants (On/Go, 76.4% and 71.0%; iHealth, 73.0%, and 71.0%; QuickVue, 84.3%, and 74.3%; BinaxNOW, 69.7%, and 71.0%; and InBios, 66.3% and 64.5%, respectively) [ 45 ]. However, most of these studies only evaluated the sensitivity and specificity for detecting Omicron B.1.1529 but not for detecting currently circulating subvariants [ 45 , 46 , 49 ]. A study reported that most of the Omicron subvariants accumulated amino acid substitutions in the N protein [ 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…Apart from the studies that reported the decline of the RAT for Omicron detection, other studies claimed that some of the currently available RATs are not affected by the emergence of Omicron [45][46][47][48], particularly when being used to assess the samples with high viral load. The DIAGNOVIR SARS-CoV-2 ultra-rapid antigen test, for example, was reported to demonstrate high performance in detecting most SARS-CoV-2 variants including Wuhan, Alpha (B1.17), Beta (B.1.351), Delta (B.1.617.2), and Omicron (B.1.1529) [49]. A study on several currently available RAT kits demonstrated a similar level of sensitivity to Omicron and non-Omicron variants (On/Go, 76.4% and 71.0%; iHealth, 73.0%, and 71.0%; QuickVue, 84.3%, and 74.3%; BinaxNOW, 69.7%, and 71.0%; and InBios, 66.3% and 64.5%, respectively) [45].…”
Section: Plos Onementioning
confidence: 99%